PERTUMBUHAN TANAMAN EBONI (Diospyros celebica Bakh) PADA BERBAGAI NAUNGAN - Rauf, Abd; Umar, Husain; Wardah, Wardah (Universitas Tadulako, 2016)
Ebony (Diospyros celebica Bakh.) is a luxirious wood that very popular either in or abroad. The regeneration level of ebony in nature is low enough, it is caused of its semitolerant characterictic and its slowly growth,which on its seedling level, ebony needs shelter plants and at the time of secondary branch formed, it needs light intensity that should increase along its growth. The aim of the research was to find out the growth of Ebony plant in various shelter. The allocation time was began on May to August 2015. The research used Group Randomized design that consisted of 4 treatments and 2 groups as follow: slope tilt 50and 40, so there were 8 unit of trials. One unit of trial consisted of 5 seedling that the total planted was 4 × 2 × 5 = 40 seedling. The result of the research showed that shelter treatment of 90% (N4) resulted the increase of the highest number of Ebony seedling leaves was (`2,7sheets) and the smallest 0% (N1) as (0,02 sheet),the shelter treatment of (70% (N3) gave a better response to the height increase of ebony seedling was (1,01 cm) and the lowest 0% (N1) was (0,09 cm), and the width of ebony seedling leaves was (25,39 cm2) and the lowest 0% (N1) was (0,79 cm2), and the shelter treatment of 40% (N2)gave a better reponse to the diameter increase of ebony stem seedling was (0,35 mm) and the lowest of 0% (N1) was (0,02 mm).Keywords : Ebony, Diospyros celebica Bakh,Shelter, Growth.